Caracterização do perfil de microvesículas circulantes em pacientes com trombocitemia essencial - Alves, Emanuela Vitória Barbosa (2023)
Essential thrombocythemia (ET) is characterized by clonal proliferation of megakaryocytes in the bone marrow, which results in an increase in the number of circulating platelets. ET has a higher prevalence in females between the ages of 50 and 60 years. Microvesicles (MVs) are a heterogeneous group of vesicles, originating in the plasma membrane of normal or neoplastic cells, their content and function depend on the cell of origin, their structure is formed by a lipid bilayer and inside there are lipids, proteins, mRNA and miRNA. Studies indicate that MVs participate in fundamental processes in the multiplication and formation of the microenvironment of neoplastic cells and play an important role in the development of cancer in the body. The aim of this study is to characterize the profile of circulating microvesicles in patients diagnosed with Essential Thrombocythemia treated at the Fundação Hospitalar de Hematologia e Hemoterapia do Amazonas. We will evaluate the medical records of patients to collect sociodemographic and clinical characteristics, perform laboratory tests for hematological analysis, biochemical analysis, and hemostasis tests. To determine the cellular origin of the MVs, the flow cytometry technique will be used with specific antibodies: progenitor cells (CD34), myeloid cells (CD13, CD33 and CD117), leukocytes (CD45), dendritic cells (CD11c), monocytes (CD14) , neutrophils (CD16 and CD66b), T lymphocytes (CD3), B lymphocytes (CD19), NK cells (CD56), platelets (CD41a), erythrocytes (CD235a) and endothelial cells (CD51/61). The group of patients with ET on hydroxyurea treatment had a high level of total circulating microvesicles and populations of MVs CD34, CD13, CD11c, CD14, CD16, CD66b, CD3, CD19, CD56 and CD235a. The high level of these MVs demonstrates that different populations of MVs may be involved in the pathogenesis of ET. Hydroxyurea treatment seems to play a crucial role in decreasing MVs, the present study found an association between the decrease in the number of circulating MVs with increasing treatment time.